PENGELOLAAN USAHA HULU MINYAK DAN GAS BUMI SEBELUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-X/2012 - Riza, Dola (Normative Jurnal Ilmiah Hukum, 2024)
The Constitutional Court stated that there were 9 articles that were unconstitutional in the Oil and Gas Law. After the Constitutional Court's decision the government was deemed inconsistent in carrying out the Constitutional Court's decision. The formulation of the problem in this research is 1). How is the management of oil and gas before the Constitutional Court Decision Number 36 / PUU-X / 2012. Type of research used is normative legal research, The research approach used is approach to legislation and conceptual approaches. The legal material used is primary legal materials, secondary law materials and tertiary legal materials. The technique of collecting the legal material used is study documents. The technique of analysis of legal materials used is qualitative analysis techniques. Based on the results of the study can be concluded that Oil and gas management prior to the birth of the Constitutional Court Decision is carried out by the oil and gas implementing agency, where the oil and gas implementing agency represents the country in conducting civil relations with business entities or permanent business entities.